Diferences in epidemic spread patterns of norovirus and infuenza seasons ofGermany: an application of optical fow analysis in epidemiology (2020)
This analysis presents data from a new perspective ofering key insights into the spread patterns of norovirus and infuenza epidemic events. We utilize optic fow analysis to gain an informed overview of a wealth of statistical epidemiological data and identify trends in movement of infuenza waves throughout Germany on the NUTS 3 level (413 locations) which maps municipalities on European level. We show that Infuenza and norovirus seasonal outbreak events have a highly distinct pattern. We investigate the quantitative statistical properties of the epidemic patterns and fnd a shifted distribution in the time between infuenza and norovirus seasonal peaks of reported infections over one decade. These fndings align with key biological features of both pathogens as shown in the course of this analysis.